COOPERATIVE HEGEMONIC MASCULINITY IN DISNEY’S MOANA: NEOLIBERAL GENDER POLITCS AND THE RECONFIGURATION OF PATRIARCHAL AUTHORITY - Previani Nuzuliansyah; Inayatul Chusna (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study examines the representation of hegemonic masculinity in Disney’s animated film Moana (2016). Drawing on Connell’s theory of hegemonic masculinity, this research employs a qualitative constructionist approach to examine how male authority operates within a seemingly progressive narrative. The analysis focuses on the characters of Moana and Maui, whose dominance, confidence, and technical competence embody traditional masculine ideals. Although the film promotes themes of collaboration and empowerment, Maui’s mentorship continues to shape Moana’s growth, subtly reaffirming male centrality. His transformation from an authoritative figure to a supportive mentor reflects the adaptive nature of hegemonic masculinity, which redefines itself as emotionally intelligent and cooperative rather than overtly dominant. The findings reveal that while Moana advances female empowerment, it simultaneously preserves patriarchal values through subtle mechanisms of validation and guidance. By embedding male authority within a cooperative framework, the film perpetuates traditional gender hierarchies in a modernized and socially acceptable form. This study contributes to media and gender studies by extending Connell’s theory of hegemonic masculinity into the realm of contemporary animated cinema, showing how masculine dominance is recalibrated into culturally acceptable forms of guidance, partnership, and emotional vulnerability without relinquishing structural authority.